Air pollutant emissions from fossil fuel consumption in China: Current status and future predictions. (15th June 2020) - Lu, Yan; Shao, Min; Zheng, Chenghang; Ji, Haibo; Gao, Xiang; Wang, Qin'geng
Abstract: Energy consumption, especially the combustion of fossil fuels, is the main source of air pollutants emissions. Emissions of SO2, NOx, CO, PM10, PM2.5, BC, OC, and NH3 from fossil fuel consumption in different sectors were estimated for 2015, 2020, and 2030 based on updated and projected activity data and emission factors (EFs) in this study. The emissions in 2015 were: 22.8 Tg SO2, 19.8 Tg NOx, 140.7 Tg CO, 8.6 Tg PM10, 5.4 Tg PM2.5, 1.5 Tg BC, 2.1 Tg OC, and 0.3 Tg NH3 . The industrial sector and coal consumption was the major source of pollutants except NH3, and the contribution of transportation to NOx, CO, and NH3 cannot be ignored. In the future, significant decline in industrial emissions may occur and the transportation sector may be the dominant source of emissions. It was predicted that the emissions of NOx will show an upward trend in 2030 due to increased vehicle emissions, while the range of areas with high emission fluxes will gradually narrow and the emissions will shift from point to nonpoint sources. The predicted results indicated that the emphasis of future mitigation policies should not only focus on the industrial sector and heavily polluted areas where emission fluxes will remain intensive, but also focus on the pollution control of the transportation sector to prevent NOx emissions from rising in some regions. Highlights: Air pollutant emissions in China have been changing significantly. Air pollutant emissions were estimated for 2015 and projected for 2020 and 2030. Emissions from sectors show remarkable differences in growth. The tendency of emissions is a new indication to China's air quality control.